2006
DOI: 10.1123/ijsnem.16.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Iron Supplementation: Oral Tablets versus Intramuscular Injection

Abstract: Non-anemic, iron depleted women were randomly assigned to an injection group (IG) or oral group (OG) to assess which method is more efficient for increasing iron stores over a short time period. IG received a course of 5 x 2 mL intramuscular injections over 10 d, and OG received one tablet daily for 30 d. Fourteen, 21 and 28 d after commencing supplementation, ferritin concentration in OG significantly increased from baseline (means +/- standard error: 27 +/- 3 to 40 +/- 5 to 41 +/- 5 to 41 +/- 5 microg/L; P <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…For instance, it is well known that iron deficiency can impair hematologic adaptation, which left untreated can negatively impact on athletic performance (Garvican et al, 2011). However, nutritional correction of this issue via various intervention strategies has been regularly shown to have a positive impact on correcting the underlying deficiency and enhancing athlete performance (Dawson et al, 2006;Garvican et al, 2011;Woods et al, 2014).…”
Section: Therapeutic Nutritional Supplements and Prophylactic Aidsmentioning
confidence: 99%
“…For instance, it is well known that iron deficiency can impair hematologic adaptation, which left untreated can negatively impact on athletic performance (Garvican et al, 2011). However, nutritional correction of this issue via various intervention strategies has been regularly shown to have a positive impact on correcting the underlying deficiency and enhancing athlete performance (Dawson et al, 2006;Garvican et al, 2011;Woods et al, 2014).…”
Section: Therapeutic Nutritional Supplements and Prophylactic Aidsmentioning
confidence: 99%
“…In general, these come in the ferrous (ferrous fumarate, ferrous sulfate, and ferrous gluconate), or ferric form; the latter is less well tolerated (Brittenham, 2000). Athlete cohort studies show generally positive responses (40-80% increase) to long-term oral iron supplementation (8+ weeks) provided at a rate of ∼100 mg per day (Dawson et al, 2006;Garvican et al, 2014). Of interest, recent research has shown that alternate day supplementation (rather than every day), can result in a greater fractional and cumulative total iron absorption, when the same absolute dose (i.e., 60 mg of iron for 14 days consecutively vs. 28 days alternating) is provided (Stoffel et al, 2017).…”
Section: Ironmentioning
confidence: 99%
“…Such a prospect leads us to the more contemporary methods of correcting an individual's iron stores, such as intramuscular or intravenous (IV) iron supplementation. Both processes have been shown to have extremely positive and fast-acting impacts on an athlete's iron status (Dawson et al, 2006;Garvican et al, 2011;Garvican et al, 2014), likely as a result of bypassing the gut, where many known issues of iron absorption exist. Although the speed of effect is a key positive outcome of these alternative iron supplementation methods, such protocols should be reserved for athletes in desperate need of iron therapy, who appear unresponsive to more traditional approaches of dietary intervention or oral iron supplementation.…”
Section: Ironmentioning
confidence: 99%
“…However, should a faster increase in iron status be required (due to impending competition, extreme fatigue, etc), the use of an intramuscular iron injection may be considered by the sports physician. When comparing such a technique to the ingestion of oral iron tablets, it has been shown that 5×2 ml intramuscular injections of Ferrum H (equivalent to 100 mg of elemental iron), provided over a 10-day period, resulted in a significantly faster and greater increase in SF levels when compared to the ingestion of an oral iron tablet (105 mg of elemental iron), which was consumed over a 30-day period 9. Although a significantly faster way to improve the iron status of an athlete, to date, the evidence for an improvement in athletic performance from such a regime is negligible, and more research is required into this area of iron supplementation.…”
Section: Ironmentioning
confidence: 99%